Levels of cadmium in locally produced cocoa powder products available in the National Capital Region - Prado, Abigail M.; Rustia, Abigal S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
Cadmium (Cd) is a toxic environmental contaminant which occurs naturally and can accumulate in agricultural crops and hence, enter the human food chain. Cd has been detected in chocolate and other cocoa products. This study established the levels of Cd in locally available cocoa powder products in the National Capital Region. The levels of Cd were determined in locally produced cocoa powder samples (n=30) obtained from supermarkets in the National Capital Region. Cadmium levels in the cocoa powder samples (n=60) were determined by following the validated AOAC official method 999.11 for cocoa powder using flame atomic absorption spectrophotometry (F-AAS) with the following established parameters: (a) Limit of Detection (LOD) of 0.03 mg/kg; (b) Limit of Quantification (LOQ) of 0.11 mg/kg; (c) Accuracy - Linearity/Linear range with correlation coefficient (r2) of 0.8927; and (d) % Recovery of 92% to 104%. The Cd levels in all cocoa powder samples ranged from 0.01 to 0.052 mg/kg. Generally, the Cd levels in cocoa powder samples were lower than the proposed maximum level (ML) for cocoa powder at 4.0 mg/kg (CX/CF 16/10/9). Dietary exposure assessment of Cd in the consumption of cocoa powder as cocoa drink by Filipino consuming population with respect to national data (Philippine National Nutrition Survey) and WHO GEMS/Food Consumption Data, concluded that the estimates of dietary exposures were less than 100% of the Provisional Tolerable Monthly Intake (PTMI), 0.2250 mg/kg bw/month established by the 3rd JECFA in 2010.
Thesis Classification: P
Thesis (B.S. in Food Technology)---University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Cadmium -- Philippines; Cocoa -- Philippines -- Metro Manila; Cocoa -- Cadmium content